The social organization of university students' first heterosexual intercourse in Slovenia - Kogovšek, Tina (Teorija in praksa, 2015)
The article presents the results of the first national study on the intimate lifestyles of university students in Slovenia, focusing on the analysis of the social conditions in wich the first heterosexual intercourse (FHI) is placed in. After taking account of relevant theories on social changes in the sphere of intimacy and sexsuality in late modernity (Giddens, Bauman), the authors argue that it is largely the social forms of sexsuality and not the content that have changed significantly. The article concentrates on two research questions: first, whether the experience of the FHI is closer to Gidden's concept of a pure relationship or to Bauman's pure sexsual encounter and whether the type of social relationship in wich the FHI was embedded is linked to its content (especially the motives and feelings accompaying it); and second, whether the social relationship in which students experienced their FHI is indeed free from social constraints (e.g. gender, social status and religiosity). Data confirm strong link between the type of relationship in which FHI happened and the modalities of this sexual experience. FHIs embedded in committed relationships (CRs) differ from those occurring in uncommitted relationship (URs) although the differences had various strengths.
Keywords: Contraception; Kontracepcija; sexual intercourse; Sexuality; Slovenia; Slovenija; Spolnost; student; Students; študenti; Študentje; študentke